Revisiting Interreligious Relationship and Minority Groups in Indonesia - Irawan, Irawan (Edugama: Jurnal Kependidikan dan Sosial Keagamaan, 2018)
Indonesia is a democratic country. Every believer is free to worship according to their beliefs. But in fact, it is still found disharmonious relationship and violence acts between Islamic minority groups or other minority adherents and Islamic majority groups. Based on Setara Institute, there are still 201 violations (2017) and 208 (2016) in this country. Then, bom terrors to minorities groups still happen (On May 13, 2018 in Surabaya). This article aims to describe the meaning of interreligious relationship, the portrait of interreligious relationship in Indonesia, and how to foster tolerance and defend minority groups in the context of Indonesian Islam. This article is analyzed by using “the theory of interreligious relationship perspective”. This paper concluded that: the first, to avoid religious conflict and violent acts, everyone must return to the motto Bhinneka Tunggal Ika (Unity in Diversity). The second, Islamic minority groups or minority religious adherents are not allowed to be oppressed by any other groups because of different belief. The violent acts are contrary to the 1945 Constitution and Pancasila. Everyone has right to live in the Unitary State of the Republic of Indonesia (NKRI). The third, imams, ulamas, and religious leaders can function to be deterrent in religion conflict and violent acts by doing dialogue or win-win solution while referring to Islamic traditions. This study is hoped to be researched and explored more comprehensive in the future in order harmonious religious life in Indonesia will be better.